Gumdrop angel - Cawthon, Scott 1971-; Waggener, Andrea Rains 1960- (Cawthon, Scott 1971- Five nights at Freddy's. Fazbear frights, 2021)
A string of bad luck you can't seem to shake... for Angel, Hudson, and Sergio, it's an all too familiar feeling. Repulsed by her spoiled stepsister's lavish birthday party, Angel exacts a hasty and ill-fated revenge. Hudson's young life is littered with tragedy and broken dreams, but a well-paying security job might just be all he needs to turn things around. Sergio acquires a unique novelty toy that instantly brings good luck, but is the toy really leading him to happiness... or to a more monstrous end?